The Effect of Positive Thinking Training on Reduction of Depression, Stress and Anxiety of Juvenile Delinquents - Zandvakili, M; Jalilvand, M; Nikmanesh, Z (International Journal of Medical Toxicology and Forensic Medicine, 2014)
Background: The positive psychology always seeks to recognize and describe the pleasure and subjective well-being. The main issue of this field is to improve the well-being and recognize the positive aspects in order to reinforce them to prevent and develop the mental health. The aim of the present study is to investigate the effect of positive thinking training workshop on reduction of depression, stress and anxiety of juveniles at Correction and Rehabilitation Centers. Methods: The quasi-experimental method was used in this study and the depression, anxiety and stress scale (DASS-21) was used. Forty one subjects participated in this research and were divided into two homogeneous groups based on their pretest scores and were randomly included in the experimental and control groups. The positive thinking training workshop was performed for 10 sessions within three weeks on experimental group and after that the posttest and after one month the follow up test were performed. Results: The results have shown that the positive thinking training courses have effects on reduction of depression and anxiety. But it had not effects on stress in the follow up study. Conclusion: Thus, this training can be used for reduction of depression and anxiety of juvenile at Correction and Rehabilitation Center.